ЗАСТОСУВАННЯ МЕТОДУ ВИКОРИСТАННЯ ГЕОМЕТРИЧНИХ ФРАКТАЛІВ ДЛЯ ОПТИМАЛЬНОГО РОЗМІЩЕННЯ СЕНСОРІВ ПРИ ЕКОЛОГІЧНОМУ МОНІТОРИНГУ - Гордійко, Наталія Олександрівна; Лисенко, Олександр Іванович; Томашевська, Тетяна Володимирівна (Збірник матеріалів Міжнародної науково-технічної конференції «ПЕРСПЕКТИВИ ТЕЛЕКОМУНІКАЦІЙ», 2017)
Method Of Using Geometrical Fractal for Optimal Sensor Allocation for Environmental Monitoring This article deals with a specific example of solving the problem of optimal allocation of sensors in the system of ecological monitoring for various geometric areas. For the location of sensors proposed method of using geometrical fractals: placing the system sensors in cell centers fractal geometric object selected accordance with its shape geometry area.